Quality of life, problems, and needs of disease-free breast cancer survivors 5 years after diagnosis - Schmidt, Martina; Wiskemann, Joachim; Steindorf, Karen (Quality of life research, 2018)
After cancer treatment, it is desirable to maintain or regain a high quality of life (QoL) and the ability to accomplish everyday tasks well. Therefore, we substantiated the scarce knowledge regarding long-term QoL after breast cancer, burdensome problems, and unmet needs for more support.